Assembly for solid oxide fuel cell
By using a ferrite stainless steel matrix with specific chemical components in the connector of a solid oxide fuel cell and coating precious metal particles, the problems of increased resistance and chromium poisoning in high temperature environments are solved, and excellent conductivity and anti-chromium poisoning properties are achieved.
Patent Information
- Application Number
- CN202380061413.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-31
- Filing Date
- 2023-04-24
- Publication Date
- 2025-04-01
AI Technical Summary
The connectors of the existing solid oxide fuel cells have increased resistance in high temperature environments, decreased performance, and are susceptible to chromium poisoning, resulting in deterioration of electrode performance.
Ferrite stainless steel is used as the matrix to control the chromium content between 14.0% and 32.0%, aluminum content between 2.50% and 7.00%, and precious metal particles are coated on the surface of the matrix, with an average particle size between 1 micron and 10 microns, a coating thickness between 0.5 microns and 10 microns, and a surface coverage of 1.0% or above.
It realizes excellent conductivity under high temperature environments, effectively suppresses chromium poisoning, and improves the performance stability of the electrode.
Smart Images

Figure CN119744314A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a component for a solid oxide fuel cell, which has excellent electrical conductivity and resistance to chromium poisoning. Background Art
[0002] Fuel cells emit less harmful gases and have higher power generation efficiency, and are therefore expected to be widely used in various power generation systems including large-scale power generation, cogeneration systems, and automotive power supplies.
[0003] Among them, solid oxide fuel cells (SOFCs) have the advantages of being able to operate at high temperatures of 500°C to 900°C, not requiring a catalyst for electrode reactions, and being able to use a variety of fuel gases. Therefore, solid oxide fuel cells are attracting attention as the next generation of energy.
[0004] In the components of solid oxide fuel cells, the interconnect (also called "separator" or "bipolar plate") is used to form gas flow paths and connect adjacent cells in the fuel cell stack. The interconnect is also responsible for transmitting current. Therefore, the interconnect needs to be conductive. Various metal materials have been proposed for such interconnects of solid oxide fuel cells.
[0005] For example, Japanese Patent Laid-Open No. JP 2003-187828 A (PTL 1) describes:
[0006] "Ferritic stainless steel for solid oxide fuel cell components, containing, by mass%, 0.03% or less carbon (C), 2.0% or less manganese (Mn), 0.6% or less nickel (Ni), 0.03% or less nitrogen (N), 10.0% to 32.0% chromium (Cr), and at least one of the following: 2.0% or less silicon (Si) or 6.0% or less aluminum (Al), the total of the above is 1.5% or more, and the balance is mainly composed of Fe."
[0007] WO 2018 / 008658 A (PTL 2) describes:
[0008] “A ferritic stainless steel containing, in terms of mass%, 0.030% or less C, 1.00% or less Si, 1.00% or less Mn, 0.045% or less phosphorus (P), 0.0030% or less sulfur (S), 20.0% to 25.0% Cr, 0.3% to 2.0% molybdenum (Mo), 0.040% or less N, 0.50% or less aluminum (Al), 0.20% or less vanadium (V), and 0.001% to 0.500% niobium (Nb) and / or 0.001% to 0.50% titanium (Ti), with the balance being Fe and unavoidable impurities.”
[0009] US 9765421 B2 (PTL 3) describes:
[0010] "A method useful in an electrode of an electrochemical device comprises depositing a noble metal on an upper surface of a corrosion resistant metal substrate".
[0011] Citation List
[0012] Patent Literature
[0013] [Patent Document 1] Japanese Patent Application Laid-Open No. JP2003-187828A
[0014] [Patent Document 2] WO2018 / 008658A
[0015] [Patent Document 3] US 9765421 B2 Summary of the invention
[0016] The metal material described in PTL 1 contains a large amount of Si and / or Al in its chemical composition. However, when the Si and Al content is high, oxides with low conductivity such as silicon dioxide and aluminum oxide will be formed on the surface of the metal material in the high temperature environment used in solid oxide fuel cells. Therefore, when the metal material described in PTL 1 is used in the connector of a solid oxide fuel cell, the resistance will increase and the battery performance will decrease.
[0017] In addition, the chemical composition of the metal material described in PTL 2 contains a certain amount of Cr, so an oxide coating mainly composed of Cr-based oxides such as Cr2O3 is formed on the surface of the metal material. However, in the high-temperature environment used in solid oxide fuel cells, Cr-based oxides will volatilize and adhere to the electrodes, resulting in a decrease in electrode performance (hereinafter referred to as Cr poisoning). In fact, PTL 2 does not consider the suppression of Cr poisoning. Therefore, when the metal material described in PTL 2 is used in components of solid oxide fuel cells, especially connectors, there may be a decrease in electrode performance due to Cr poisoning.
[0018] Likewise, suppression of Cr poisoning is not considered in PTL 3. Therefore, when the metal material described in PTL 3 is used for components of a solid oxide fuel cell, particularly a connector, there is a concern that Cr poisoning may lead to degradation of electrode performance.
[0019] Therefore, it would be helpful to provide a component for a solid oxide fuel cell having excellent electrical conductivity and resistance to chromium poisoning.
[0020] In order to solve the above problems, we conducted in-depth research.
[0021] We found that these problems can be solved by:
[0022] (1) With ferritic stainless steel as the matrix, its chemical composition is: Cr content is controlled within the range of 14.0% to 32.0% (mass percentage), Al content is controlled within the range of 2.50% to 7.00% (mass percentage), where
[0023] (2) The surface of the substrate is coated with precious metal particles, wherein the precious metal particles have:
[0024] The average particle size is 1 μm or more and 10 μm or less;
[0025] The coating thickness on the substrate (hereinafter also referred to as "coating thickness") is 0.5 μm or more and 10 μm or less; and
[0026] The surface coverage on the substrate (hereinafter also simply referred to as "surface coverage") is 1.0% or more.
[0027] The reason for this is considered to be as follows.
[0028] In a ferritic stainless steel having a chemical composition in which the Cr content is 14.0% to 32.0% (mass percentage) and the Al content is 2.50% to 7.00% (mass percentage), an alumina surface layer is formed on the surface of the ferritic stainless steel in a high temperature environment in which a solid oxide fuel cell is used, and the formation of Cr-based oxides is prevented. As a result, the volatilization of the Cr-based oxides is suppressed and Cr poisoning of the electrode is prevented. However, the electrical conductivity of alumina is low, and if alumina is formed on the surface of the substrate, the desired conductivity cannot be obtained. In order to overcome this limitation, precious metal particles are deposited and fused with the surface of the ferritic stainless steel containing Al, thereby generating a current path through the alumina surface layer. Then, by controlling the average particle size and coating thickness of the precious metal particles within the above range, the current path can be maintained by the continuous presence of the precious metal particles between the alumina formed on the surface of the substrate. If the surface coverage of the precious metal particles is higher than a certain level, a sufficient current path can be ensured and good conductivity can be obtained. In view of the above, we believe that by simultaneously satisfying the above characteristics (1) and (2), excellent electrical conductivity and excellent resistance to chromium poisoning can be achieved at the same time.
[0029] The present disclosure is based upon these findings and further studies.
[0030] Therefore, we provide the following aspects.
[0031] 1. A component for a solid oxide fuel cell, comprising:
[0032] A substrate and precious metal particles located on the surface of the substrate, wherein the substrate is ferritic stainless steel, and the chemical composition of the ferritic stainless steel contains (consists of) the following components by mass percentage:
[0033] Carbon: 0.025% or less,
[0034] Silicon: 0.05% to 1.00%,
[0035] Manganese: 0.05% to 1.00%,
[0036] Phosphorus: 0.050% or less,
[0037] Sulfur: 0.010% or less,
[0038] Chromium: 14.0% to 32.0%,
[0039] Aluminum: 2.50% to 7.00%,
[0040] Nickel: 0.01% to 1.00%, and
[0041] Nitrogen: 0.025% or less,
[0042] The balance is iron and unavoidable impurities, and
[0043] Among them, the average particle size of the precious metal particles is 1 micron or more and 10 microns or less; the coating thickness of the precious metal particles on the substrate is 0.5 microns or more and 10 microns or less; and the surface coverage of the precious metal particles on the substrate is 1.0% or more.
[0044] 2. A component for a solid oxide fuel cell according to aspect 1 above, wherein the precious metal particles comprise at least one selected from the group consisting of gold, silver, platinum, palladium, rhodium, iridium, ruthenium and osmium, and alloy particles of at least one of the group consisting of gold, silver, platinum, palladium, rhodium, iridium, ruthenium and osmium.
[0045] 3. The component for a solid oxide fuel cell according to aspect 1 above, wherein the chemical composition of the ferritic stainless steel further contains at least one selected from the following group in terms of mass percentage:
[0046] Molybdenum: 3.00% or less,
[0047] Copper: 0.50% or less,
[0048] Cobalt: 1.00 % or less,
[0049] Tungsten: 3.00 % or less,
[0050] Titanium: 0.30% or less,
[0051] Niobium: 1.00% or less,
[0052] Vanadium: 0.50% or less,
[0053] Zirconium: 0.50% or less,
[0054] Boron: 0.0050% or less,
[0055] Calcium: 0.0050% or less,
[0056] Magnesium: 0.0100% or less, and
[0057] Rare earth elements: 0.20% or less.
[0058] 4. The component for a solid oxide fuel cell according to aspect 2 above, wherein the chemical composition of the ferritic stainless steel further contains at least one selected from the following group by mass percentage:
[0059] Molybdenum: 3.00% or less,
[0060] Copper: 0.50% or less,
[0061] Cobalt: 1.00 % or less,
[0062] Tungsten: 3.00 % or less,
[0063] Titanium: 0.30% or less,
[0064] Niobium: 1.00% or less,
[0065] Vanadium: 0.50% or less,
[0066] Zirconium: 0.50% or less,
[0067] Boron: 0.0050% or less,
[0068] Calcium: 0.0050% or less,
[0069] Magnesium: 0.0100% or less, and
[0070] Rare earth elements: 0.20% or less.
[0071] According to the present invention, a solid oxide fuel cell component having excellent electrical conductivity and resistance to chromium poisoning can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0072] Figure 1 A SEM micrograph of sample No. A3 according to an example is shown. DETAILED DESCRIPTION
[0073] Some embodiments of the present disclosure are described below.
[0074] (1) Matrix
[0075] First, the chemical composition of the ferritic stainless steel (hereinafter also referred to as "base ferritic stainless steel") used as the substrate of the solid oxide fuel cell assembly according to one embodiment of the present invention is introduced. Unless otherwise specified, the symbols "%" below indicating the chemical composition are all mass percentages (%).
[0076] 1. Carbon C: 0.025% or less
[0077] C has the effect of improving the high temperature strength of steel. In order to achieve this effect, the C content is preferably 0.001% or more. However, if the C content exceeds 0.025%, the toughness and formability of the steel will decrease. Therefore, the C content is 0.025% or less. The C content is preferably 0.010% or less.
[0078] 2. Silicon Si: 0.05% to 1.00%
[0079] Si has the effect of improving the oxidation resistance of steel. In order to obtain this effect, the Si content is 0.05% or more. However, if the Si content exceeds 1.00%, silicon dioxide with low conductivity is formed at the interface between the oxide film formed at high temperature and the base metal, resulting in reduced conductivity. Therefore, the Si content is 1.00% or less. The Si content is preferably 0.20% or less.
[0080] 3. Manganese Mn: 0.05% to 1.00%
[0081] Mn has the effect of improving the peeling resistance of the oxide film formed at high temperature. In order to exert this effect, the Mn content is 0.05% or more. However, if the Mn content exceeds 1.00%, the oxide film may grow abnormally, resulting in a decrease in oxidation resistance. In addition, the thickening of the oxide film may cause a decrease in conductivity. Therefore, the Mn content is 1.00% or less. The Mn content is preferably 0.20% or less.
[0082] 4. Phosphorus P: 0.050% or less
[0083] P is a harmful element that reduces the toughness of steel. Therefore, the lower the P content, the better. Therefore, the P content is 0.050% or less. The P content is preferably 0.030% or less. The lower limit of the P content is not particularly limited. However, since excessive dephosphorization leads to increased costs, the P content is preferably 0.010% or more.
[0084] 5. Sulfur S: 0.010% or less
[0085] S is a harmful element that adversely affects the formability and oxidation resistance of steel. Therefore, the lower the S content, the better. Therefore, the S content is 0.010% or less. The S content is preferably 0.005% or less. The lower limit of the S content is not particularly limited. However, since excessive desulfurization leads to increased costs, the S content is preferably 0.0001% or more.
[0086] 6. Chromium Cr: 14.0% to 32.0%
[0087] Cr is an important element that helps to form aluminum oxide on the surface of the base ferritic stainless steel. In order to obtain this effect, the Cr content is 14.0% or more. The Cr content is preferably 18.0% or more. However, if the Cr content exceeds 32.0%, the toughness and formability of the steel will decrease. Therefore, the Cr content is 32.0% or less. The Cr content is preferably 22.0% or less.
[0088] 7. Aluminum: 2.50% to 7.00%
[0089] Al is an important element that forms aluminum oxide on the surface of the base ferritic stainless steel and inhibits the formation of Cr-based oxides. That is, Al has the effect of inhibiting the volatilization of Cr and preventing Cr poisoning of the electrode. In order to obtain this effect, the Al content is 2.50% or more. The Al content is preferably 5.00% or more, and more preferably 5.50% or more. On the other hand, if the Al content exceeds 7.00%, the toughness of the steel decreases and manufacturing becomes difficult. Therefore, the Al content is 7.00% or less. The Al content is preferably 6.5% or less.
[0090] 8. Nickel Ni: 0.01% to 1.00%
[0091] Ni has the effect of improving the toughness and oxidation resistance of steel. In order to obtain this effect, the Ni content is 0.01% or more. On the other hand, if the Ni content exceeds 1.00%, it will form at high temperatures. Phase, oxidation resistance will be reduced. Therefore, the Ni content is 1.00% or less. The Ni content is preferably less than 0.20%.
[0092] 9. Nitrogen N: 0.025% or less
[0093] N is an element that reduces the toughness and formability of steel. Therefore, a lower N content is preferred. In particular, if the N content exceeds 0.025%, the toughness and formability may be significantly reduced. Therefore, the N content is 0.025% or less. The N content is preferably less than 0.010%. There is no particular restriction on the lower limit of the N content. However, since excessive denitrification leads to increased costs, the N content is preferably 0.001% or higher.
[0094] Optionally, the chemical composition of the matrix ferritic stainless steel used in the solid oxide fuel cell assembly according to one embodiment of the present invention may also include at least one selected from the following group:
[0095] Molybdenum Mo: 3.00% or less,
[0096] Copper Cu: 0.50% or less,
[0097] Cobalt Co: 1.00% or less,
[0098] Tungsten W: 3.00% or less,
[0099] Titanium Ti: 0.30% or less,
[0100] Niobium Nb: 1.00% or less,
[0101] Vanadium V: 0.50% or less,
[0102] Zirconium Zr: 0.50% or less,
[0103] Boron B: 0.0050% or less,
[0104] Calcium Ca: 0.0050% or less,
[0105] Magnesium Mg: 0.0100 % or less, and
[0106] Rare earth elements REM: 0.20% or less.
[0107] 10. Molybdenum: 3.00% or less
[0108] Mo has the effect of improving the high temperature strength and oxidation resistance of steel. In order to obtain this effect, the Mo content is preferably 0.01% or more. The Mo content is preferably 1.20% or more. On the other hand, if the Mo content exceeds 3.00%, the steel becomes harder and the manufacturability becomes poor. Therefore, when Mo is contained, the Mo content is 3.00% or less. The Mo content is preferably 2.30% or less.
[0109] 11. Copper Cu: 0.50% or less
[0110] Cu has the effect of improving the high temperature strength of steel by precipitating in steel. In order to obtain this effect, the Cu content is preferably 0.01% or more. However, if the Cu content exceeds 0.50%, the toughness decreases and the manufacturability deteriorates. Therefore, when Cu is contained, the Cu content is 0.50% or less.
[0111] 12. Cobalt: 1.00% or less
[0112] Co has the effect of improving the toughness of steel. In order to obtain this effect, the Co content is preferably 0.01% or more. On the other hand, if the Co content exceeds 1.00%, the formability of the steel decreases. Therefore, when Co is contained, the Co content is 1.00% or less. The Co content is preferably 0.30% or less.
[0113] 13. Tungsten W: 3.00% or less
[0114] W has the effect of improving the high temperature strength of steel. In order to obtain this effect, the W content is preferably 0.01% or more. On the other hand, if the W content exceeds 3.00%, the steel becomes hard, resulting in difficulty in manufacturing. Therefore, when W is contained, the W content is 3.00% or less. The W content is preferably 1.00% or less.
[0115] 14. Titanium Ti: 0.30% or less
[0116] Ti has the effect of improving the formability of steel. In order to obtain this effect, the Ti content is preferably 0.01% or more. However, if the Ti content exceeds 0.30%, coarse Ti (C, N) precipitation will occur, resulting in reduced toughness of the steel. Oxidation resistance is also reduced. Therefore, when Ti is contained, the Ti content is 0.30% or less. The Ti content is preferably 0.15% or less, and more preferably 0.05% or less.
[0117] 15. Niobium Nb: 1.00% or less
[0118] Nb has the effect of improving the high temperature strength of steel. In order to obtain this effect, the Nb content is preferably 0.01% or more. However, if the Nb content exceeds 1.00%, the steel becomes hard and the manufacturability deteriorates. Therefore, when Nb is contained, the Nb content is 1.00% or less. The Nb content is preferably 0.40% or less.
[0119] 16. Vanadium V: 0.50% or less
[0120] V has the effect of improving the formability and oxidation resistance of steel. In order to obtain this effect, the V content is preferably 0.01% or more. However, if the V content exceeds 0.50%, coarse V (C and N) precipitation occurs, resulting in a decrease in the toughness of the steel. Therefore, when V is contained, the V content is 0.50% or less. The V content is preferably 0.10% or less.
[0121] 17. Zirconium Zr: 0.50% or less
[0122] Zr has the effect of improving oxidation resistance. In order to obtain this effect, the Zr content is preferably 0.01% or more. However, if the Zr content exceeds 0.50%, Zr intermetallic compounds precipitate and the toughness of the steel decreases. Therefore, when Zr is contained, the Zr content is 0.50% or less. The Zr content is preferably 0.10% or less.
[0123] 18. Boron B: 0.0050% or less
[0124] B has the effect of improving the toughness of steel. In order to obtain this effect, the B content is preferably 0.0002% or more. On the other hand, if the B content exceeds 0.0050%, BN is generated and the formability of the steel decreases. Therefore, when B is contained, the B content is 0.0050% or less. The B content is preferably 0.0010% or less.
[0125] 19. Calcium Ca: 0.0050% or less
[0126] Ca has the effect of improving oxidation resistance. In order to obtain this effect, the Ca content is preferably 0.0002% or more. However, if the Ca content exceeds 0.0050%, surface defects are easily generated in the steel. Therefore, when Ca is contained, the Ca content is 0.0050% or less. The Ca content is preferably 0.0020% or less.
[0127] 20. Magnesium Mg: 0.0100% or less
[0128] Mg has the effect of improving oxidation resistance. In order to obtain this effect, the Mg content is 0.0002% or more. However, if the Mg content exceeds 0.0100%, surface defects are easily generated in the steel. Therefore, when Mg is contained, the Mg content is 0.0100% or less. The Mg content is preferably 0.0025% or less.
[0129] 21. Rare earth elements REM: 0.20% or less.
[0130] REM is a general term for scandium (Sc), yttrium (Y), lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm) and hafnium (Hf). REM has the effect of improving the adhesion of alumina to the surface of the matrix ferritic stainless steel and improving oxidation resistance. In order to obtain this effect, the content of REM is preferably 0.01% or more, more preferably 0.06% or more. On the other hand, if the content of REM exceeds 0.20%, the steel is prone to surface defects. Therefore, when REM is contained, the content of REM is 0.20% or less. The content of REM is preferably 0.10% or less.
[0131] The remaining elements other than the above elements are iron Fe and inevitable impurities.
[0132] Preferably, the microstructure of the matrix ferritic stainless steel has a ferrite phase volume fraction of 95% or more. The volume fraction of the residual microstructure is preferably 5% or less. The residual microstructure includes an austenite phase and a martensite phase. The matrix ferritic stainless steel may have a ferrite single-phase structure (volume fraction: 100%).
[0133] At this time, identification of the microstructure (calculation of the volume fraction of the ferrite phase) is performed as follows.
[0134] The test piece for cross-sectional observation was removed from the base ferritic stainless steel and etched with a saturated hydrochloric acid solution of picric acid. Then, 10 fields of view of the test piece for cross-sectional observation were observed under an optical microscope at a magnification of 100 times, and the shape of the microstructure and the etching intensity were analyzed to identify the ferrite phase. Then, the volume fraction of the ferrite phase in each field of view was determined by image processing, and the obtained results were averaged. The volume fraction of the ferrite phase was calculated, excluding intermetallic compounds, precipitates, and inclusions. The volume fraction of the residual microstructure was calculated by subtracting the volume fraction of the ferrite phase from 100%.
[0135] An example of a solid oxide fuel cell assembly according to an embodiment of the present invention includes, in addition to a material processed into a part shape (eg, a connector), a green sheet before being processed into a part shape (eg, a plate-shaped material).
[0136] The base ferritic stainless steel may be formed into, for example, a plate shape (e.g., a steel plate) or a component shape. The thickness of the base ferritic stainless steel formed into a plate shape (e.g., a steel plate) or a component shape is not particularly limited. However, from the viewpoint of chromium poisoning resistance and formability, the suitable thickness of the base ferritic stainless steel is 0.01 mm to 10.0 mm. The thickness of the base ferritic stainless steel is preferably 0.03 mm or more. The thickness of the base ferritic stainless steel is preferably 8.0 mm or less, and more preferably 2.0 mm or less.
[0137] (2) Precious metal particles
[0138] Next, the noble metal fine particles coated on the surface of the base ferritic stainless steel will be described.
[0139] The noble metal particles are particles of elements such as gold (Au), silver (Ag), platinum (Pt), palladium (Pd), rhodium (Rh), iridium (Ir), ruthenium (Ru), osmium (Os), and alloy particles of these elements. Among them, noble metals with high melting points (>1500°C) are preferred, such as platinum (Pt), iridium (Ir), rhodium (Rh), palladium (Pd), osmium (Os), osmium (Ru), etc., and ruthenium is particularly preferred. High melting point noble metals will ensure the long-term working stability of SOFC at high operating temperatures. The noble metal particles can be composed of one of the above elements, or two or more of the above elements. In the latter case, for example, the noble metal particles can be a mixture of particles of two or more of the above elements, or particles of alloys of two or more of the above elements.
[0140] The precious metal particles coated on the surface of the substrate ferritic stainless steel exist on the surface in an island-like morphology. In this case, each portion exhibiting such an island-like morphology is referred to as a "particle". Maintaining the island-like morphology of the precious metal coating, rather than conventional continuous layer coating, can a) reduce the amount of precious metal used, and b) minimize the stress between the coating and the substrate due to the mismatch in thermal expansion coefficients, which is necessary to avoid coating delamination in high-temperature SOFC applications.
[0141] As described above, it is extremely important to simultaneously control the average particle size, coating thickness and surface coverage of the noble metal fine particles coated on the surface of the base ferritic stainless steel within the following ranges, respectively.
[0142] Average particle size of precious metal particles: 1 μm or more, 10 μm or less
[0143] If the average particle size of the noble metal particles is less than 1 μm, it is difficult to reliably bond (or fuse) the noble metal particles to the base ferritic stainless steel. On the other hand, if the average particle size of the noble metal particles exceeds 10 μm, the stress generated between the noble metal particles and the base due to the mismatch of thermal expansion coefficients may cause the noble metal particles to delaminate from the base. When the noble metal particles are peeled off, the current path disappears and good conductivity cannot be obtained. Therefore, the average particle size of the noble metal particles is 1 μm or more and 10 μm or less.
[0144] The average particle size of the precious metal particles is the average value of the equivalent diameter of a circle calculated based on the area of each precious metal particle observed on the substrate surface. Specifically, the measurement is performed by the method described in the example section described later. The average particle size of the precious metal particles is calculated by excluding particles with an equivalent circle diameter of less than 0.1 μm, which particles do not substantially contribute to ensuring the current path. Similarly, the coating thickness and surface coverage of the precious metal particles described later are also calculated by excluding particles with an equivalent circle diameter of less than 0.1 μm.
[0145] Coating thickness of precious metal particles: 0.5 μm or more, 10 μm or less
[0146] If the coating thickness of the precious metal particles is less than 0.5 μm, then in the high temperature environment used in the solid oxide fuel cell, alumina will be thickly formed on the surface of the base ferritic stainless steel, covering the precious metal particles. As a result, the current path disappears and good conductivity cannot be obtained. On the other hand, if the coating thickness of the precious metal particles exceeds 10 μm, the precious metal particles are easily peeled off from the surface of the base ferritic stainless steel. When the precious metal particles are peeled off, the current path disappears and good conductivity cannot be obtained. Therefore, the coating thickness of the precious metal particles is 0.5 μm or more and 10 μm or less.
[0147] The coating thickness of the noble metal fine particles is the average value of the maximum length of the noble metal fine particles in the direction perpendicular to the substrate surface (hereinafter also referred to as "the direction perpendicular to the substrate surface"), and is specifically measured by the method described in the Examples section described later.
[0148] Precious metal particle surface coverage: 1.0% or more
[0149] When the surface coverage of the noble metal particles is less than 1.0%, the current path is insufficient to provide good conductivity. Therefore, the surface coverage of the noble metal particles is 1.0% or greater. The surface coverage of the noble metal particles is preferably 5.0% or greater. The upper limit of the surface coverage of the noble metal particles is not particularly limited and can be as high as 95%. However, the higher the surface coverage of the noble metal particles, the higher the cost. Therefore, the surface coverage of the noble metal particles is preferably less than 80%.
[0150] The surface coverage of precious metal particles is the surface coverage of precious metal particles on the substrate surface, which is determined by the following factors:
[0151] [Surface coverage of precious metal particles (%)] =
[0152] [Area of the substrate surface covered by precious metal particles (mm 2 )] / [surface area of substrate (mm2)]×100.
[0153] (3) Production method
[0154] Next, an exemplary method of producing a solid oxide fuel cell assembly according to one embodiment of the present disclosure will be described.
[0155] First, a matrix ferritic stainless steel used as a matrix is prepared. For example, molten steel is prepared by smelting in a smelting furnace such as a converter or an electric furnace. Then, the molten steel is secondary refined by ladle refining or vacuum refining to adjust the chemical composition as described above. Then, the molten steel is made into a semi-finished product (slab) by continuous casting or ingot casting and blooming. From the perspective of productivity and quality, continuous casting is preferred. Then, the semi-finished product (slab) is hot rolled to obtain a hot-rolled steel plate. The hot-rolled steel plate can also be further subjected to additional processes such as hot-rolled plate annealing and / or pickling. Hereinafter, when only hot-rolled steel plates are mentioned, not only hot-rolled steel plates (including steel plates obtained after pickling and / or other treatments of hot-rolled steel plates) are included, but also so-called hot-rolled annealed steel plates (including steel plates obtained after hot-rolled steel plates are subjected to hot-rolled plate annealing treatment, and steel plates obtained after further pickling and / or other treatments of steel plates after hot-rolled plate annealing treatment). Depending on the application, the hot-rolled steel sheet can be used directly as a product without undergoing subsequent processes such as cold rolling (hereinafter also referred to as a "hot-rolled product"). For example, in the case of manufacturing a casing of a solid oxide fuel cell, the hot-rolled steel sheet can be used directly as a substrate.
[0156] Then, the hot-rolled steel sheet is cold rolled to obtain a cold-rolled steel sheet. Then, the cold-rolled steel sheet is subjected to other subsequent processes such as finish annealing (cold-rolled sheet annealing) and pickling to obtain a product such as a cold-rolled annealed sheet (hereinafter also referred to as a "cold-rolled product"). Examples of cold-rolled annealed sheets include steel sheets obtained by performing final annealing (cold-rolled sheet annealing) on the cold-rolled steel sheet, and steel sheets obtained by further performing pickling and / or other additional processes on the steel sheet after the final annealing (cold-rolled sheet annealing). There is no particular restriction on the gas pressure used for annealing the cold-rolled sheet. For example, bright annealing (BA) can be carried out in a reducing gas such as hydrogen, in which case pickling can be omitted. Before pickling, descaling can be performed by shot peening or mechanical descaling methods.
[0157] The base ferritic stainless steel can be prepared as described above.
[0158] The above steps can be carried out according to conventional methods under corresponding conditions.
[0159] For example, when the semi-finished product (slab) is heated before hot rolling, the heating temperature is preferably 1050°C to 1250°C.
[0160] The hot-rolled sheet annealing is preferably performed in a temperature range of 800°C to 1150°C by continuous annealing.
[0161] Cold rolling can be performed once or twice or more, with annealing performed between the two cold rollings. From the viewpoint of productivity and required quality, it is preferred to perform cold rolling twice or more with annealing performed in between. The total rolling reduction ratio of cold rolling is preferably 50% or more, more preferably 60% or more.
[0162] The final annealing (cold rolled sheet annealing) is preferably performed in a continuous annealing method within a temperature range of 850°C to 1100°C, and more preferably within a temperature range of 900°C to 1050°C.
[0163] In addition, depending on the application, the final annealing may be followed by temper rolling or other processes to adjust the shape of the steel plate, the roughness of the steel plate surface, and the material properties.
[0164] Then, the above-mentioned noble metal particles are coated on the surface of the substrate ferritic stainless steel prepared in this way. As a coating method, for example, a thermal spraying method can be used. The thermal spraying material can be a noble metal element salt solution or a metal particle suspension. The material can be heated by flame, plasma or electric arc, and gas sprayed to apply the coating.
[0165] After coating, heat treatment may be performed at a temperature of 100° C. to 500° C. for a time of 1 second to 10 hours to improve the bonding force between the noble metal particles and the matrix ferritic stainless steel.
[0166] Optionally, before or after coating, the base ferritic stainless steel may be further processed, such as cutting, bending, expanding, stretching or otherwise processed, and formed into a desired shape, such as the shape of a connector, by a forming process. Coating may be performed before, after, or both before and after the forming process.
[0167] Example
[0168] Steel samples with the chemical composition listed in Table 1 (the balance is Fe and unavoidable impurities) were smelted in a vacuum melting furnace and cast into 30 kg steel ingots. Each ingot was heated to 1250 ° C and then hot rolled into slabs with a thickness of 30 mm. After the slabs were heated to 1150 ° C, the slabs were hot rolled to obtain hot-rolled steel plates. The hot-rolled steel plates were annealed at a temperature of 850 ° C to 1100 ° C and then ground to obtain hot-rolled annealed plates with a thickness of 4.0 mm. The hot-rolled annealed plates were then cold rolled to obtain cold-rolled steel plates. The cold-rolled steel plates were then finally annealed at a temperature of 850 ° C to 1100 ° C to obtain cold-rolled annealed plates with a thickness of 1.0 mm. The front and back sides of the cold-rolled annealed plates were then polished with #800 sandpaper and degreased with acetone. A test sample was taken from each cold-rolled annealed sheet for cross-sectional optical microscopic examination, etched with a picric acid saturated hydrochloric acid solution, and observed under an optical microscope at 100 times magnification to identify the microstructure of the cold-rolled annealed sheet. The results confirmed that each sample had a ferrite single-phase structure (volume fraction of ferrite phase: 100%).
[0169] The obtained cold rolled annealed sheets were coated with ruthenium metal particles by flame spraying to prepare a plurality of samples No. A1 to A5 and B2 to B3 listed in Table 2. For comparison, cold rolled annealed sheet samples No. B1 and B4 in Table 2 without noble metal particle coating were prepared.
[0170] The average particle size, coating thickness and surface coverage of the precious metal particles were then measured for these samples as described below. The results are listed in Table 2.
[0171] Specifically, 10 arbitrary locations on the surface of each sample were observed at a magnification of 1000 times using a scanning electron microscope (hereinafter also referred to as "SEM"). Then, in the micrograph taken by the SEM (hereinafter referred to as "SEM micrograph"), the precious metal particles coated on the surface of the substrate were identified by an image interpretation method, and the area of each precious metal particle was measured. Then, the equivalent diameter calculated based on the area of the precious metal particles was determined. Then, the average value of the results was used as the average particle size of the precious metal particles. As a reference, Figure 1 A SEM micrograph of sample No. A3 is shown in FIG.
[0172] The total area of the noble metal particles in the SEM micrograph is defined as the area of the substrate surface covered by the noble metal particles (mm 2 ), and then divide the total area of the precious metal particles in each SEM photograph by the total area of the observation area in the SEM micrograph to obtain the surface coverage of the precious metal particles.
[0173] The coating thickness of the precious metal particles is measured by grinding the precious metal particles and the substrate in a direction perpendicular to the substrate surface using a focused ion beam system (hereinafter referred to as "FIB") of Ga ions to prepare a sample for cross-sectional observation of the precious metal particles, and observing the cross section (observed surface) at a magnification of 10,000 times using an SEM. Specifically, a test sample is taken from each sample for cross-sectional observation so that any five precious metal particles are included in the observation object, and the observation plane is microphotographed using an SEM to determine the maximum length of each of the five precious metal particles in the direction perpendicular to the substrate surface. In this case, the maximum length corresponds to the distance between the upper and lower edges of the precious metal particles on the observation plane in the direction perpendicular to the substrate surface. The lower edge corresponds to one of the edges of the precious metal particles on one side close to the substrate surface in the direction perpendicular to the substrate surface, and the upper edge corresponds to the other edge on the opposite side. Then, the average value of the maximum length is taken as the coating thickness of the precious metal particles.
[0174] The samples were also evaluated for chromium poisoning resistance and electrical conductivity as described below. The results are listed in Table 2.
[0175] <Electrical conductivity evaluation>
[0176] Each sample was cut into a size of 1.0mm×20mm×20mm and subjected to oxidation treatment in air at 700°C for 2000 hours. A 5mm×5mm Pt paste was applied to the front and back surfaces of each sample after oxidation treatment. Each sample was then kept at 700°C for 30 minutes to dry. A Pt mesh (10mm×10mm) was then placed on the area on the front and back surfaces of each sample where the Pt paste was applied. The Pt mesh was made by connecting the Pt wire for current application and the Pt wire for voltage measurement by spot welding. Each sample was then placed in a heating furnace heated to 700°C to apply 0.1kgf / cm 2 The load was maintained for 30 minutes. During the holding period at 700°C, a current was applied to each sample at a current density of 0.5 A / cm2, and the voltage at this time was measured to determine the resistance (contact resistivity). Then, the resistance value was measured n = 3 (i.e., three times) for each sample, the measurement results were averaged, and the conductivity was evaluated according to the following criteria:
[0177] Good: Average resistance is 0.1 Ω·cm 2 or lower, and
[0178] Poor: Average resistance value exceeds 0.1 Ω·cm 2 .
[0179] <Anti-chromium poisoning>
[0180] Each sample was cut into a size of 1.0 mm × 20 mm × 20 mm and placed in a quartz sample holder of a quartz tube furnace. The sample holder was placed in the center of the tube furnace. Quartz wool was placed downstream of the sample holder to collect Cr evaporated from the sample. Then, the temperature in the tube furnace was maintained at 700 ° C for 100 hours while 15 vol.% H2O + Air flows through the tube furnace. After being maintained as above, all Cr attached to the sample holder and quartz wool is dissolved in the acid solution, and the Cr concentration in the acid solution is measured using an inductively coupled plasma mass spectrometer (ICP-MS). Then, the amount of Cr contained in the acid solution is calculated based on the Cr concentration and the amount of the acid solution. Then, the amount of Cr evaporated from each sample is calculated by dividing the amount of Cr in the acid solution by the surface area of the sample. Then, the anti-chromium poisoning ability is evaluated according to the following criteria:
[0181] Good: Cr evaporation amount is 1.0 mg / cm 2 The following, as well as
[0182] Poor: Cr evaporation exceeds 1.0 mg / cm 2 .
[0183] Table 1
[0184]
[0185] Table 2
[0186]
[0187] As can be seen from Table 2, all examples exhibit excellent electrical conductivity and excellent resistance to chromium poisoning.
[0188] On the other hand, in the comparative example No. B1, the surface of the substrate is not covered with the noble metal fine particles, and sufficient conductivity cannot be obtained.
[0189] In Example No. B2, the surface coverage of the noble metal fine particles was below the appropriate range, and sufficient conductivity could not be obtained.
[0190] In Example No. B3, the Al content of the base ferritic stainless steel is below the appropriate range, and sufficient resistance to chromium poisoning cannot be obtained.
[0191] In Example No. B4, the Al content of the base ferritic stainless steel is below the appropriate range, and sufficient resistance to chromium poisoning cannot be obtained.
[0192] The above examples are for illustrative purposes only and are in no way to be construed as limiting. Although reference is made to various embodiments, the words used herein are descriptive and illustrative, rather than restrictive. Furthermore, although reference is made to specific devices, materials, and embodiments, the details disclosed herein are not to be limited. Rather, the embodiments extend to all functionally equivalent structures, methods, and uses, such as within the scope of the appended claims.
[0193] Industrial Applicability
[0194] The solid oxide fuel cell assembly according to the invention is particularly suitable for use as an interconnect. The solid oxide fuel cell assembly according to the invention is also suitable for use as a component of other fuel cells, such as a solid oxide electrolyzer cell (also known as SOEC) or a solid oxide reversible cell (also known as SORC).
Claims
1. A component for a solid oxide fuel cell, comprising: A substrate and precious metal particles located on the surface of the substrate, wherein the substrate is ferritic stainless steel, and the chemical composition of the ferritic stainless steel contains, by mass percentage: Carbon: 0.025% or less, Silicon: 0.05% to 1.00%, Manganese: 0.05% to 1.00%, Phosphorus: 0.050% or less, Sulfur: 0.010% or less, Chromium: 14.0% to 32.0%, Aluminum: 2.50% to 7.00%, Nickel: 0.01% to 1.00%, and Nitrogen: 0.025% or less, The balance is iron and unavoidable impurities, and Among them, the average particle size of the precious metal particles is 1 micron or more and 10 microns or less; the coating thickness of the precious metal particles on the substrate is 0.5 microns or more and 10 microns or less; and the surface coverage of the precious metal particles on the substrate is 1.0% or more.
2. The component for a solid oxide fuel cell according to claim 1, wherein the precious metal particles comprise at least one selected from the group consisting of gold, silver, platinum, palladium, rhodium, iridium, ruthenium and osmium, and alloy particles of at least one of the group consisting of gold, silver, platinum, palladium, rhodium, iridium, ruthenium and osmium.
3. The component for a solid oxide fuel cell according to claim 1, wherein the chemical composition of the ferritic stainless steel further contains at least one selected from the following group in terms of mass percentage: Molybdenum: 3.00% or less, Copper: 0.50% or less, Cobalt: 1.00 % or less, Tungsten: 3.00 % or less, Titanium: 0.30% or less, Niobium: 1.00% or less, Vanadium: 0.50% or less, Zirconium: 0.50% or less, Boron: 0.0050% or less, Calcium: 0.0050% or less, Magnesium: 0.0100% or less, and Rare earth elements: 0.20% or less.
4. The component for a solid oxide fuel cell according to claim 2, wherein the chemical composition of the ferritic stainless steel further contains at least one selected from the following group by mass percentage: Molybdenum: 3.00% or less, Copper: 0.50% or less, Cobalt: 1.00 % or less, Tungsten: 3.00 % or less, Titanium: 0.30% or less, Niobium: 1.00% or less, Vanadium: 0.50% or less, Zirconium: 0.50% or less, Boron: 0.0050% or less, Calcium: 0.0050% or less, Magnesium: 0.0100% or less, and Rare earth elements: 0.20% or less.
Citation Information
Patent Citations
Ferritic stainless steel for solid oxide type fuel cell member
JP2003187828A
Highly electrically conductive surfaces for electrochemical applications
US9765421B2
Ferritic stainless steel, steel sheet thereof, and methods for producing these
WO2018008658A1